Perancangan Kontrol Multivariabel Sistem Pengaduk Pemurnian Uranium - Karsid, Karsid; Aziz, Rofan (Jurnal Teknologi Terapan, 2016)
Stirrer system has analyzed the homogeneity of Uranium Penurnian Installation unit which serves to change the yellow cake (natural uranium) into uranium UO2 powder. in this system of natural uranium in the form of effluent UO2 (NO3)2 maintained homogeneity, with a surface elevation level fixed tank. Uranium purification system involves two (2) tanks interplay output, so the output is obtained in accordance with the sett-point value, then the system needs to be in decoupling. Then the control system is applied to the height of the tank using decouling Level control with shift method eigenvalues.